What are the health consequences associated with differences in medical malpractice liability laws? An instrumental variable analysis of surgery effects on health outcomes for proximal humeral facture across states with different liability rules - Brian Chen; Sarah Floyd; Dakshu Jindal; Cole Chapman; John Brooks (BMC, 2022)
Abstract Background States enacted tort reforms to lower medical malpractice liability, which are associated with higher surgery rates among Medicare patients with shoulder conditions. Surgery in this group often entails tradeoffs between improved health and increased risk of morbidity and mortality. We assessed whether differences in surgery rates across states with different liability rules are associated with surgical outcomes among Medicare patients with proximal humeral fracture. Methods We obtained data for 67,966 Medicare beneficiaries with a diagnosis of proximal humeral fracture in 2011. Outcome measures included adverse events, mortality, and treatment success rates, defined as surviving the treatment period with < $300 in shoulder-related expenditures. We used existing state-level tort reform rules as instruments for surgical treatment and separately as predictors to answer our research question, both for the full cohort and for stratified subgroups based on age and general health status measured by Charlson Comorbidity Index and Function-Related Indicators. Results We found a 0.32 percentage-point increase (p < 0.05) in treatment success and a 0.21 percentage-point increase (p < 0.01) in mortality for every 1 percentage-point increase in surgery rates among patients in states with lower liability risk. In subgroup analyses, mortality increased among more vulnerable patients, by 0.29 percentage-point (p < 0.01) for patients with Charlson Comorbidity Index >  = 2 and by 0.45 percentage-point (p < 0.01) among those patients with Function-Related Indicator scores >  = 2. On the other hand, treatment success increased in patients with lower Function-Related Index scores (< 2) by 0.54 percentage-point (p < 0.001). However, younger Medicare patients (< 80 years) experienced an increase in both mortality (0.28 percentage-point, p < 0.01) and treatment success (0.89 percentage-point, p < 0.01). The reduced-form estimates are consistent with our instrumental variable results. Conclusions A tradeoff exists between increased mortality risk and increased treatment success across states with different malpractice risk levels. These results varied across patient subgroups, with more vulnerable patients generally bearing the brunt of the increased mortality and less vulnerable patients enjoying increased success rates. These findings highlight the important risk-reward scenario associated with different liability environments, especially among patients with different health status.